CLARIFYING THE BALANCE SHEET. - McMullen, Stewart Yarwood (The Accounting Review, 1951)
Abstract The article analyses and interprets the discussions of the American Accounting Association's Committee on Concepts and Standards on corporate financial statements. The committee proposed that it be authorized to issue a numbered series of supplementary statements. Some of the recommendations on reserves and retained income confirm current practice, while others recommend ways in which published financial statement practices could be improved. The discussions of the Committee in the general area of reserves is analyzed in terms of the six major questions. These questions include, is "reserve" a useful tool in published financial statements? The statements by the committee recommends that the term reserve be eliminated from published statements. According to the author the Committee could find no reasons to justify a recommendation that the profession seek to standardize a definition which would be in permanent conflict with the dictionary meaning. A spirited discussion took place with respect to so-called self-insurance reserves. The author remarks that there is no unanimity in the Committee as to whether casualty losses accrue, statistically or otherwise.